2017
DOI: 10.1371/journal.pone.0186191
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and clinicopathological value of Twist expression in breast cancer: A meta-analysis

Abstract: BackgroundDespite initial indications that the transcription factor Twist could be used as a breast cancer prognostic marker, there still exists some controversy about its reliability. Thus, the aim of the present study was to assess the relationship between Twist expression and prognosis in breast carcinoma.Materials and methodsWe identified eligible studies that reported an association between Twist expression and breast cancer prognosis by searching the literature in PubMed, Embase, the Cochrane Library, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
3
12
3
Order By: Relevance
“…Still, we found that the few patients (5%) with a twist positive PT had a shorter DRFi, compared to patients with a twist negative PT. This is in line with results obtained previously, where positive expression of twist has been associated with poor outcome of breast cancer patients [44,46], though an association between positive twist expression and a superior overall survival also has been described [33]. Our results might seem paradoxical, though twist is a transcription factor involved in multiple signaling pathways and could be a more biologically relevant marker to study compared to the three EMT effector markers included in our study [47,48].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Still, we found that the few patients (5%) with a twist positive PT had a shorter DRFi, compared to patients with a twist negative PT. This is in line with results obtained previously, where positive expression of twist has been associated with poor outcome of breast cancer patients [44,46], though an association between positive twist expression and a superior overall survival also has been described [33]. Our results might seem paradoxical, though twist is a transcription factor involved in multiple signaling pathways and could be a more biologically relevant marker to study compared to the three EMT effector markers included in our study [47,48].…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, in this study, we did not see any difference by marker status in relation to prognosis in terms of DRFi. Expression of twist in PTs has also previously been linked to various clinical parameters [44,45]. However, we did not find a significant association with any tumor or patient characteristic analyzed in this study.…”
Section: Discussioncontrasting
confidence: 90%
“…Overexpression of TWIST and SLUG has also been observed in stromal tumor cells (64). However, the association of TWIST expression with disease-free survival and overall survival has not been consistently observed throughout these studies (63)(64)(65). Moreover, in a sample of 100 breast tumors, Nodal expression was associated with VM formation and VE-cadherin expression in a subgroup of tumors.…”
Section: Relationship Between Cscs Vm and The Epithelial-mesenchymalmentioning
confidence: 98%
“…Currently, the principal role of tumour markers in patients radically treated for BC and its metastases involves the early and timely diagnosis of systemic disease recurrence (13,14). Several studies have shown that elevation of serum tumour markers occurs significantly in advance of diagnosis of BC recurrence using radiodiagnostic methods (15,16).…”
Section: Discussionmentioning
confidence: 99%